Kinerja Saham Perusahaan Sebelum dan Sesudah Stock-Split di Bursa Efek Indonesia - Isnurhadi Isnurhadi (Program Studi Magister Manajemen FE Unsri, 2010)
This research is an even study that was conducted by analyzing the performance of stocks 5 days before and after stock’s split. The objective of this research is to investigate and analyze the change of the stocks’ performance after being split. In this case, the stock’s performance is measured in term of stock price, stock return, and stock trading volume. To analyze the change in performance of stock split, signaling theory is used where stock split is deemed as a signal to investors that the company has a good prospect in the future. The sample comprises of companies listed at the Indonesian Exchange that experienced stock split during a period of 2006 to 2008. Sample is selected using purposive sampling. 37 companies’ stocks are selected conforming to the criteria. Using paired t-test, the data was analyzed to test whether any significant difference in performance before and after stock split.This research found that there is a significant difference in stock performance before and after stock split. There is a significant price change before and after stock split. The trading volume before the split is also significantly different from after the split with the p-value of 0.006. Finally, in term of stock return there is a significant difference between returns 5 days before split and returns 5 days after split with the p-value of 0.024. In short, the hypotheses that there are significant performances differences in term of stock price, stock return and stock trading volume are supported.Keyword : Stock performance, stock price, stock return and stock trading volume